2011
DOI: 10.1007/s13197-011-0483-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of putrescine and carnauba wax on functional and sensory quality of pomegranate (Punica granatum L.) fruits during storage

Abstract: Functional properties (anthocyanins, antioxidant, ascorbic acid and tannin) and sensory score were determined in pomegranate fruits at two storage temperatures (3 and 5 °C) after treatment with 2 mM putrescine and 1 : 10 carnauba wax (carnauba wax : water). The treatments (putrescine and carnauba wax) were given by immersion method followed by storage up to 60 days. Both treatments retained significantly higher anthocyanins, antioxidant, ascorbic acid, tannin and sensory qualities as compared with control frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 28 publications
11
19
0
Order By: Relevance
“…However, no significant difference in the ascorbic acid content was found between control and MAP-treated pomegranates after 180 days of cold storage and 180 + 3 days SL at 20 C (Tables 1 and 2). Our findings are in agreement with those of Arendse et al (2014), Barman et al (2014) and Abd-elghany et al (2012) who reported a gradual decrease in ascorbic acid content in pomegranates during storage. The reduction in the level of ascorbic acid might be the result of delayed biosynthesis or fast degradation of ascorbic acid in MAP-stored fruit (Khan and Singh, 2008).…”
Section: Resultssupporting
confidence: 94%
“…However, no significant difference in the ascorbic acid content was found between control and MAP-treated pomegranates after 180 days of cold storage and 180 + 3 days SL at 20 C (Tables 1 and 2). Our findings are in agreement with those of Arendse et al (2014), Barman et al (2014) and Abd-elghany et al (2012) who reported a gradual decrease in ascorbic acid content in pomegranates during storage. The reduction in the level of ascorbic acid might be the result of delayed biosynthesis or fast degradation of ascorbic acid in MAP-stored fruit (Khan and Singh, 2008).…”
Section: Resultssupporting
confidence: 94%
“…It appears that the hydroxyl groups of phenolic compounds in PE act as an antioxidant (Park et al, ). Similar to our study, Barman, Asrey, Pal, Kaur, and Jha () reported that carnauba wax‐coated pomegranate exhibit less anthocyanin loss because of the decrease in oxygen levels caused by wax coating. Overall, these results suggest that DAPG coating containing PE is most effective at maintaining the quality of “Kyoho” grape berries during storage.…”
Section: Resultssupporting
confidence: 91%
“…Antioxidant capacity of plant produce is mainly contributed by the presence of pigments, vitamins and polyphenolic compounds (Barman et al 2011c). The reason for higher retention of antioxidant capacity in sodium hydroxide treated mango fruits might be explained by higher content of carotenoids and phenolics compounds.…”
Section: Total Phenolics Content and Antioxidant Capacitymentioning
confidence: 99%